Perencanaan Pembelajaran dengan Pemilihan Model Pembelajaran Project Based Learning, Inquiry Based Learning dan Metode Pembelajaran Ceramah dan Diskusi pada Kurikulum Merdeka - Ainun Mardiana; Nur Rezky Asman; Bahri Bahri (Dinamika Pembelajaran : Jurnal Pendidikan dan bahasa, 2024)
This study aims to test the effectiveness of the Project-Based Learning (PjBL) learning model with the discussion method in the experimental class compared to the Inquiry-Based Learning (IBL) combined with the lecture method in the control class in improving student learning outcomes in Economics. The method used was a quasi-experiment with a pre-test and post-test design, involving 30 grade X students in each group. The results showed that the application of PjBL with discussion provided a more significant increase in student learning outcomes compared to the IBL model with lectures. The PjBL model encourages students to be active, creative, and collaborative in learning, while the lecture method in IBL is more passive. In conclusion, the PjBL model with discussion is recommended to improve the quality of learning, in accordance with the Merdeka Curriculum approach which emphasizes interactive and contextual learning experiences.